Screening anti-cancer compounds from medicinal Malaysian plants - Ahmad Raus, Raha; Johari, Yusuf; Amid, Azura (IIUM Press, 2011)
In the fight against cancer. no,·el chemotherapeutic agems arc constanlly being sought to complement cxisting dTlJlls. In this study. 110-10 methanolic cxtracts prepared from seven tropical plants "'ith. eth.nomedical uses were tesled for th.eir c)'loto~ic ability in "itro against cancer cell lines. The plants studied were Carico papaya (papaya). Co/l'Ils bl"ml'i (ali·ati), Cosmos calldalll)· (uJam raja). "-'CIIS deltoidea (rna. OOlek), Pip"I" sm·WIIII/VSIIIll (kaduk), PIIle/'M indica (beluntas), and l'I"emlllu curdifloru (bcbuas). The c)'lolOxicity screening tesl, SRB (sulforhodamine B) was calTied out to detennine plants wilh potential amicancer properties. Results indicated that P. sonuentosllflI and P. cordijloru exlracis dcmonslr4[OO signifiean[ c)'101oxicily against MCn cell line where the IC", were 125 ilgfml and 113 ilgfmL. respectively, and a[ the same lime: showed less aclh-ilies against nonnal cells. Wilh re:spc:ct [0 Ihese results, P. sarmenflUum and P. r:ordif/oro eX!T1lCIS could be studied further fOJ [heir po[enlialto lTeal cance-r.